Implementasi Website Profil sebagai Media Informasi pada Mi Mathlaul Huda Rancagong - Muhamad Kamil Fatih; Lilis Roudhotul Jannah; Syerikha Ananda (GLOBAL SCIENTS PUBLISHER, 2026)
The development of information technology has encouraged educational institutions to utilize digital media as a means of information dissemination. MI Mathlaul Huda Rancagong still uses conventional media, resulting in less optimal information delivery. This study aims to implement a school profile website as a web-based information medium using the Waterfall method. The website was developed using PHP and MySQL and tested using Black Box Testing. The results show that the implemented website is able to provide centralized school information, including school profiles, news, galleries, activity schedules, announcements, and contact information. Therefore, the implemented website can improve the effectiveness of information dissemination to the public.